Effects of Varying Methodologies on Grain Particle Size Analysis - J. R. Kalivoda; C. K. Jones; C. R. Stark (Kansas Agricultural Experiment Station Research Reports, 2015)
Particle size reduction is an important component of feed manufacturing that impacts pellet quality, feed flowability, and pig feed efficiency. The correct determination of particle size is important for feed manufacturers, nutritionists, and pork producers to meet target specifications. The current method for determining the geometric mean diameter (dgw) and geometric standard deviation (Sgw) of grains has been published by the ANSI/ASAE S319.4. This method controls many variables, including the suggested quantity of initial material and the type, number, and size of sieves. However, the method allows for variation in shake time, sieve agitators, and the use of a flow agent. Therefore, the objectives of this experiment were: 1) to determine which method of particle size analysis best estimates the particle size of various cereal grains, and 2) assess analytical variation within each method. Eighteen samples of corn, sorghum, or wheat were ground and analyzed using different variations of the standard particle size analysis method. Treatments were arranged in a 5 × 3 factorial design with five sieving methods: 1) 10-minute shake time with sieve agitators and no flow agent; 2) 10-minute shake time with sieve agitators and flow agent; 3) 15-minute shake time with no sieve agitators or flow agent; 4) 15-minute shake time with sieve agitators and no flow agent; or 5) 15-minute shake time with sieve agitators and flow agent conducted in three grains — corn, sorghum, or wheat. There were four replicates per treatment. Results for dgw and Sgw were calculated according to both standard methods S319.2 and S319.4. The analytical method that resulted in the finest dgw and greatest Sgw was considered desirable because it is presumably representative of the largest quantity of particles moved through the appropriate sieve. There was no analytical method × grain type interaction for dgw, so it was removed from the model. Analytical method affected (P<0.0001) dgw and Sgw measured by both standards. Inclusion of sieve agitators and flow agent resulted in the finest dgw, regardless of sieving time. Inclusion of flow agent reduced (P<0.05) the mean particle size by 32 or 36μm when shaken for 10 or 15 minutes, respectively, compared to the same sample analyzed without flow agent. Flow agent was also an important factor to alter Sgw. Because the flow agent increased the quantity of very fine particles collected in the pan, Sgw was substantially greater (P<0.05) when flow agent was included in the method. Particle size of corn and sorghum ground using the same mill parameters was similar (P>0.05), but wheat ground using the same mill parameters was 120 to 104μm larger (P<0.05) compared to corn or sorghum, respectively. In conclusion, both sieve agitators and flow agent should be included when conducting particle size analysis, but only 10 minutes of shake time is required. Wheat ground using the same hammermill settings as corn and sorghum is approximately 100μm larger in particle size.
Keywords: corn; feed; grain; methodology; particle size analysis